Immobilized Lentivirus Vector on Chondroitin Sulfate-Hyaluronate Acid-Silk Fibroin Hybrid Scaffold for Tissue-Engineered Ligament-Bone Junction. (12th June 2014) - Sun, Liguo; Li, Hongguo; Qu, Ling; Zhu, Rui; Fan, Xiangli; Xue, Yingsen; Xie, Zhenghong; Fan, Hongbin
Abstract : The lack of a fibrocartilage layer between graft and bone remains the leading cause of graft failure after anterior cruciate ligament (ACL) reconstruction. The objective of this study was to develop a gene-modified silk cable-reinforced chondroitin sulfate-hyaluronate acid-silk fibroin (CHS) hybrid scaffold for reconstructing the fibrocartilage layer. The scaffold was fabricated by lyophilizing the CHS mixture with braided silk cables. The scanning electronic microscopy (SEM) showed that microporous CHS sponges were formed around silk cables. Each end of scaffold was modified with lentiviral-mediated transforming growth factor- β 3 (TGF- β 3) gene. The cells on scaffold were transfected by bonded lentivirus. In vitro culture demonstrated that mesenchymal stem cells (MSCs) on scaffolds proliferated vigorously and produced abundant collagen. The transcription levels of cartilage-specific genes also increased with culture time. After 2 weeks, the MSCs were distributed uniformly throughout scaffold. Deposited collagen was also found to increase. The chondral differentiation of MSCs was verified by expressions of collagen II and TGF- β 3 genes in mRNA and protein level. Histology also confirmed the production of cartilage extracellular matrix (ECM) components. The results demonstrated that gene-modified silk cable-reinforced CHS scaffold was capable of supporting cell proliferation and differentiation to reconstruct the cartilage layer of interface.